Longitudinal, 3D Imaging of Collagen Remodeling in Murine Hypertrophic Scars In Vivo using Polarization-sensitive Optical Frequency Domain Imaging - Lo, William C. Y. (J Invest Dermatol, 2016)
Hypertrophic scars (HTS), frequently seen after traumatic injuries and surgery, remain a major clinical challenge due to the limited success of existing therapies. A significant obstacle to understanding HTS etiology is the lack of tools to monitor scar remodeling longitudinally and non-invasively. We present an in vivo, label-free technique using polarization-sensitive optical frequency domain imaging (PS-OFDI) for the 3D, longitudinal assessment of collagen remodeling in murine HTS. In this study, HTS was induced with a mechanical tension device for 4 to 10 days on incisional wounds and imaged up to one month after device removal; an excisional HTS model was also imaged at 6 months after injury to investigate deeper and more mature scars. We showed that local retardation (LR) and degree of polarization (DOP) provide a robust signature for HTS. Compared to normal skin with heterogeneous LR and low DOP, HTS was characterized by an initially low LR, which increased as collagen fibers remodeled, and a persistently high DOP. This study demonstrates that PS-OFDI offers a powerful tool to gain significant biological insights into HTS remodeling by enabling longitudinal assessment of collagen in vivo, which is critical to elucidating HTS etiology and developing more effective HTS therapies.